Effector Avr4 in Phytophthora infestans Escapes Host Immunity Mainly Through Early Termination - Waheed, Abdul; Wang, Yan-Ping; Nkurikiyimfura, Oswald; Li, Wen-Yang; Liu, Shi-Ting; Lurwanu, Yahuza; Lu, Guo-Dong; Wang, Zong-Hua; Yang, Li-Na; Zhan, Jiasui (Frontiers in Microbiology, 2021)
Effector genes play critical roles in the antagonistic interactions between plants and pathogens. However, knowledge of mutation mechanisms and evolutionary processes in effector genes and the contribution of climatic factors to the evolution of effector genes are fragmented but important in sustainable management of plant diseases and securing food supply under changing climates. Here, we used a population genetic approach to explore the evolution of Avr4 gene in Phytophthora infestans, the causal agent of potato blight. We found that the Avr4 gene exhibited a high genetic diversity generated by point mutation and sequence deletion. Frameshifts caused by a single base-pair deletion at the 194th nucleotide position generate two stop codons, truncating almost the entire C-terminal which is important for effector function and R4 recognition, in all sequences. The effector is under natural selection for adaptation supported by comparative analyses of population differentiation (FST) and isolation-by-distance between Avr4 sequences and SSR marker loci. Furthermore, we found that local air temperature was positively associated with pairwise FST in the Avr4 sequences. These results suggest that the evolution of the effector gene is influenced by local air temperature and the C-terminal truncation is one of the main mutation mechanisms in the P. infestans effector gene to circumvent the immune response of potato plants. The implication of these results to agricultural and natural sustainability in future climate condition is discussed.